Cadmium nanocluster as a safe nanocarrier: biodistribution in BALB/c mice and application to carry crocin to breast cancer cell lines - Moslem Jafarisani; S. Ali Hashemi; Nassim Faridi; Mir F. Mousavi; S. Zahra Bathaie (Open Exploration Publishing Inc., 2024)
Aim: Metal nanoclusters are emerging nanomaterials applicable for drug delivery. Here, the toxicity and oxidative stress induction of divalent cationic cadmium (Cd2+) was compared with a Cd in the form of nanocluster. Then, it was used for targeted drug delivery into breast cancer cell lines. Methods: Using a green chemistry route, a Cd nanocluster (Cd-NC) was synthesized based on bovine serum albumin. After characterization, its genotoxicity and oxidative stress induction were studied in both in vitro and in vivo. After that, it was conjugated with hyaluronic acid (HA). The efficiency of hyaloronized-Cd-CN (HA-Cd-NC) for loading and releasing crocin (Cro), an anticancer phytochemical, was studied. Finally, it was applied for cell death induction in a panel of breast cancer cell lines. Results: The comet assay results indicated that, unlike Cd2+ and potassium permanganate (KMnO4), no genotoxicity and oxidative stress was induced by Cd-NC in vitro. Then, the pharmacokinetics of this Cd-NC was studied in vivo. The data showed that Cd-NC has accumulated in the liver and excreted from the feces of mice. Unlike Cd2+, no toxicity and oxidative stress were induced by this Cd-NC in animal tissues. Then, the Cd-NC was targeted toward breast cancer cells by adding HA, a ligand for the CD44 cell surface receptor. After that, Cro was loaded on HA-Cd-NC and it was used for the treatment of a panel of human breast cancer cell lines with varying degrees of CD44. The half-maximal drug inhibitory concentration (IC50) of Cro was significantly decreased when it was loaded on HA-Cd-NC, especially in MDA-MB-468 with a higher degree of CD44 at the surface. These results indicate the higher toxicity of Cro toward breast cancers when carried out by HA-Cd-NC. Conclusions: The Cd-NC was completely safe and is a promising candidate for delivering anticancer drugs/phytochemicals into the targeted breast tumors.